2015
DOI: 10.1007/s12193-015-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality system for strengthening awareness and participation in rehabilitation for post-stroke patients

Abstract: This paper presents a system called REAPP, a virtual environment aiming at supporting upper-limb robotic neurorehabilitation for post-stroke patients. In the last few years different systems using either or both virtual environments and robots have been developed. However, such advanced systems often lack attention on the physical and psychological conditions perceived by the patient, who should be the key focus in therapies. In this context, REAPP aims not to be just an entertaining interface but also a means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In García-Betances et al ( 2015 ) an overview of recent VR technology for Alzheimer's disease applications has performed, and these systems use conventional 2D graphics display or 3D graphics indistinctly. Similarly occurs with the brain damage rehabilitation in Rose et al ( 2005 ), post-stroke studies such as Merians et al ( 2006 ), Saposnik ( 2016 ), Henderson et al ( 2007 ), Mottura et al ( 2015 ). Therefore, there is a wide panorama on virtual rehabilitation in the scientific literature.…”
Section: Introductionmentioning
confidence: 85%
“…In García-Betances et al ( 2015 ) an overview of recent VR technology for Alzheimer's disease applications has performed, and these systems use conventional 2D graphics display or 3D graphics indistinctly. Similarly occurs with the brain damage rehabilitation in Rose et al ( 2005 ), post-stroke studies such as Merians et al ( 2006 ), Saposnik ( 2016 ), Henderson et al ( 2007 ), Mottura et al ( 2015 ). Therefore, there is a wide panorama on virtual rehabilitation in the scientific literature.…”
Section: Introductionmentioning
confidence: 85%
“…Instead, it just serves as a reference to know where the other players are and to adapt the velocity to proceed together. However, some studies showed that having the possibility to customize some features may positively influence embodiment, and thus motivation to practice [73,74]. Therefore, it appears interesting to evaluate if the customization of some avatars’ characteristics, perhaps through a reward mechanism, enhances the participation and the engagement of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen participants are selected for studying the specified game-based approach in which 10 participants allotted more points to game-based training sessions than conventional therapy sessions. The AR-based rehabilitation game module for treating shoulder-related disabilities is studied by Mottura et al (2015). The paper introduces the first wearable AR game application which uses a Microsoft lens for tracking the movements of patients.…”
Section: Exoskeletons User Training Advancementsmentioning
confidence: 99%